Sideways forces on asymmetric tokamak walls during plasma disruptions. (1st August 2022) - Yanovskiy, V.; Isernia, N.; Pustovitov, V.D.; Villone, F.
Abstract: In the quarter-century since the danger of sideways force on tokamak walls during disruptions was first recognized, substantial progress has been made in understanding the connection between plasma kink and the force. Less is known, however, about the effect of the wall asymmetry on force generation. Here, we explore how irregularly situated ports lead to large sideways forces even for a symmetric driver such as a typical current quench. Further, we compare the effectiveness of both mechanisms.